A91 ECONOMIC EVALUATION OF A FECAL MICROBIOTA TRANSPLANTATION PROGRAM FOR RECURRENT CLOSTRIDIOIDES DIFFICILE INFECTION IN ALBERTA. (4th March 2021) - Yang, D Y; Mullie, T; Sun, H; Russell, L; Roach, B; Wong, K; Zhang, W; Kao, D H
Abstract: Background: Fecal microbiota transplantation (FMT) is the most effective therapy for recurrent C. difficile infection. Although studies using statistical modeling have shown FMT to be cost-effective, real-world data is lacking. Aims: To assess the impact of FMT program on the healthcare cost of recurrent C. difficile infections using real-world data from Alberta's public healthcare system. Methods: C. difficile infection patients were identified through provincial laboratory database with positive C. difficile results in Edmonton, Alberta between 2009–16. If an initial positive test was followed by ≧2 positive tests within 183 days, an individual was categorized as recurrent C. difficile infection (RCDI). Otherwise, non-recurrent C. difficile infection (non-RCDI) was assigned. Since the Edmonton FMT program was established in 2013, patients were further divided into pre-FMT (2009–12) and post-FMT (2013–16) eras. This divided patients into four study groups as outlined in Table 1. Administrative data, including inpatient stays, ambulatory or emergency room visits, outpatient prescriptions, and physician billings, were extracted. A cost of 389 was assigned to each FMT procedure to account for cost of donor screening and sample preparation. A difference in differences (DID) approach, a tool which estimates the effect of a treatment by comparing outcome difference between treatment group and control group over time, was used to analyze the impact of FMT program on the cost of RCDI. Non-RCDI patients were used as control group to account for changes in treatment costs over time. Ordinary least squares regression, with log-transformed healthcare cost as the dependent variable, was used for the analysis. Results: 4717 non-RCDI and 548 RCDI patients were identified and divided into the 4 groups (Table 1). RCDI patients were significantly older than non-RCDI patients (71.13 vs 62.49; P < 0.001). After adjusting for differences in age, sex, and baseline healthcare utilization, cost for RCDI patients were significantly lower relative to costs for non-RCDI patients in the post-FMT era. Cost of non-RCDI increased by 5, 300.08 between the pre- and post-FMT eras, while the cost of RCDI decreased by 7, 654.92 in the same time frame (Table 2). FMT program was estimated to have saved 12, 954 annually for RCDI patients at mean age, sex, and baseline cost of our overall sample. Conclusions: Our data suggest that the healthcare cost of RCDI has decreased with the introduction of an FMT program. Funding Agencies: Alberta Health Services, University of Alberta Hospital Foundation